Why Algae Release Volatile Organic Compounds—The Emission and Roles - Zuo, Zhaojiang (Frontiers in Microbiology, 2019)
A wide spectrum of volatile organic compounds (VOCs) are released from algae in aquatic ecosystems. Environmental factors such as light, temperature, nutrition conditions and abiotic stresses affect their emission. These VOCs can enhance the resistance to abiotic stresses, transfer information between algae, play allelopathic roles, and protect against predators. For homogeneous algae, the VOCs released from algal cells under stress conditions transfer stress information to other cells, and induce the acceptors to make a preparation for the upcoming stresses. For heterogeneous algae and aquatic macrophytes, the VOCs show allelopathic effects on the heterogeneous neighbors, which benefit to the emitter growth and competing for nutrients. In cyanobacterial VOCs, some compounds such as limonene, eucalyptol, β-cyclocitral, α-ionone, β-ionone and geranylacetone have been detected as the allelopathic agents. In addition, VOCs can protect the emitters from predation by predators. It can be speculated that the emission of VOCs is critical for algae coping with the complicated and changeable aquatic ecosystems.